Sharp Bounds for Fractional Conjugate Hardy Operator on Higher-Dimensional Product Spaces - Zequn Wang; Mingquan Wei; Qianjun He; Dunyan Yan (Journal of Function Spaces)
In this paper, we obtain the sharp bound for fractional conjugate Hardy operator on higher-dimensional product spaces from L1ℝn1×⋯×ℝnm to the space wLQℝn1×⋯×ℝnm and Lpℝn1×⋯×ℝnm to the space Lqℝn1×⋯×ℝnm. More generally, the operator norm of the fractional Hardy operator on higher-dimensional product spaces from LPℝn1×⋯×ℝnm to LQIℝn1×⋯×ℝnm is obtained.